Designing and fabrication of an installation PV solar modules tilting platform - Ogundimu, Emmanuel Olusegun; Akinlabi, Esther; Mgbemene, Chigbo; Jacobs, Ifeanyi (Sustainable Engineering and Innovation, 2022)
The optimum tilt-angle of a fixed photovoltaic solar panel is very important during the installation, in order to best exploit the accessible output power efficiency of the panel. The output power effectiveness of a PV solar collector is profoundly affected by its tilt-angle to the horizontal and its orientation. This is because of the detail that the sun’s angle varies at every point of time and location. The solar photovoltaic tilting platform plays a dynamic role in the installation of the solar photovoltaic panel. From one perspective, it protects the solar panel from mechanical pressures that can arise from the wind movement and the hand; it provides means of adjustment for the solar panel. The proposed solar photovoltaic tilting platform was designed for an adjustable angle capacity oscillating from 0? to 40?; the materials used for the construction of the tilting platform are capable to withstand a load of 45kg and resist a temperature of -50? F to 150? F under a maximum wind force of 3.78N. The numerous mechanisms of the PV tilting platform prototype were tested, the stability, strength, easy titling, and overall performance of the PV tilting platform were declared as satisfactory.